Analisis Laju Alir Produksi Kritis Untuk Permasalahan Water Coning Pada Sumur “DRN-22” - Nur, Dennis Ramdhan; Afifah, Rohima Sera; Firdaus, Firdaus; Luthfi, Mohammad; Manik, Nijosiho; Rahman, Muhammad Safa; Restu, Pratama Bagus (DAS Institute, 2021)
The phenomenon of water coning in oil and gas wells can lead to an undesired increase in water production, reducing hydrocarbon recovery efficiency. Determining the critical production flow rate is an essential step in controlling water movement into the production zone. This study analyzes the parameters influencing the critical flow rate, including reservoir characteristics, fluid viscosity, and well geometry. The methods employed include mathematical modeling and numerical simulations to identify the optimal production limits without triggering water coning. The results of this study provide guidance for petroleum engineers in managing well production efficiently and minimizing the negative impact of excessive water production.